2015
DOI: 10.4236/oalib.1101542
|View full text |Cite
|
Sign up to set email alerts
|

Stability and Regularization Method for Inverse Initial Value Problem of Biparabolic Equation

Abstract: We consider an inverse initial value problem of the biparabolic equation; this problem is ill-posed and the regularization methods are needed to stabilize the numerical computations. This paper firstly establishes a conditional stability of Holder type, then uses a modified regularization method to overcome its ill-posedness and gives the convergence estimate under an a-priori assumption for the exact solution. Finally, a numerical example is presented to show that this method works well.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…For the homogeneous case (when F = 0), Lakhdari [22] showed that the such problem is ill-posed and proposed a regularizing strategy based on the Kozlov-Mazýa iteration method to approximate the solution. Zhang, in [39], established a conditional stability of Holder type and used a modified regularization method to overcome the ill-posedness in this case. For the non-homogeneous problem, the very last paper [27] investigated the deterministic TVP with two cases of source function including linear and nonlinear sources.…”
Section: Introductionmentioning
confidence: 99%
“…For the homogeneous case (when F = 0), Lakhdari [22] showed that the such problem is ill-posed and proposed a regularizing strategy based on the Kozlov-Mazýa iteration method to approximate the solution. Zhang, in [39], established a conditional stability of Holder type and used a modified regularization method to overcome the ill-posedness in this case. For the non-homogeneous problem, the very last paper [27] investigated the deterministic TVP with two cases of source function including linear and nonlinear sources.…”
Section: Introductionmentioning
confidence: 99%
“…This is a typical inverse problem of operator identification [1] . We can solve the problem by gradient regularization method(GR)which was first presented in reference [2] .The method proceed with the common of inverse problem,but not attached to any particular constraint,and the solution is not affected by spatial dimension limits.Thus,it is a kind of universal method to solve the inverse problem. Based on improved GR method [5,7] ,the general finite element program is compiled,the issues such as model error and the choice of measuring points frequencies are discussed as well through numerical examples.…”
Section: Introductionmentioning
confidence: 99%
“…This is an obvious ill-posed problem [1] . Applying regularization method to construct regular functionals [2] ,based on improved gradient regularization method [5,7] ,we can get the nonlinear inverse problem iterative formula as follows:…”
mentioning
confidence: 99%